A Content Analysis on Translation Shift: How Flouting maxim, Violating maxim, and Multimodality influence the Characterization of the Main Character in the Webtoon Garden of the Dead Flower - Dwi Akbar Setiawan (Jurnal Bahasa, Sastra, dan Studi Amerika, 2026)
This paper highlights the significance of the interplay between pragmatic and multimodal approaches in constructing characterizations in Webtoon. Other studies often analyze the linguistic and visual elements separately, making this research that combines pragmatic theory and multimodal analysis in understanding character personality construction remain limited. This paper fills this gap by conducting an integrated analysis of the main character, Camellia, in the Indonesian Webtoon Garden of the Dead Flower. Using a descriptive qualitative approach, 41 dialogue panels were found where Camellia used the non-observance maxim of Grice's Cooperative Principle. It focuses on analyzing how the data of flouting and violating maxim synergize with multimodal cues. The results show that Camellia's characterization is explicitly constructed by flouting maxim of relevance and violating maxim of quality. This pragmatic strategy depicts her character as cunning and strategic yet vulnerable. The analysis also found that the multimodal cues amplify these pragmatic choices, such as expressive close-ups, camera framing, and typography. This study concludes that Camellia’s characterization is constructed together by linguistic and visual design, offering a robust model for analyzing characterization in digital narrative media.